Pengaruh Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM) dan Cash Ratio (CR) terhadap Laba Bersih pada Industri Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2017 - Siti Nurliana (Science of Management and Students Research Journal (SMS), 2019)
Siti Nurliana / 1400861201233 / Faculty Of Economi University BatangHari Jambi 2018 / The Influence Of Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM) dan Cash Ratio (CR) On The Net Income is The Banking Industri Listed in 2012-2017 / 1st Advisor Dr. Yunan Surono, SE, M.M / 2nd Advisor Fadil Iskandar, SE, M.M  The Purpose of this study was to examine the effect of Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM), and CASH RATIO (CR) on net income in the banking industry listed in 2012-2017, the author uses the Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM), and Cash Ratio (CR) as the independent variable and the related net profit variable. This research was taken because there is still a difference between one assement with another and the difference between the state of the value of the research data and the existing theory. This research conducted with used secondary data. The technique use is purposive sampling from 43 companies industrial metal are only captured 5 companies because they have a complete financial report positif earnings year 2012-2017. Methoids of analysis used multiple liniear regression analysis. Hypothesis testing performed using a tast f and t test, the level of significance (α) 5%. Analyzing data using software SPSS statistical data processing i.e 20.00 Result SPSS 20 get a multiple liniear regression equation is Y = - 0,001 + 0,520 X1 + - 0,069 X2 + 0,088 X3 + 0,769 X4 + eF test results indicate that the banking industry company variable Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM), and CASH RATIO (CR) affect the variable net income in the analysis model of the t test result (individually) indicating that the CAR variable has an effect, the NPL variable does not affect, the NIM variable has no effect while the Cash Ratio has a positive and significant to net income. Test results R Square in this study amounted to 0,578% while the remaining 42,2% is influenced by other variables not examined in this study. The results of this study can be concluded that net income has a positive effect by the CAR has no effect by the NPL has no effect by NIM and a positive influence by Cash Rati.